THE AUTHORITY OF THE REGIONAL SUPERVISORY COUNCIL IN TAKING NOTARIAL PROTOCOLS WITH A 25-YEAR TERM - Fauzan; Herlindah; Diah Aju Wisnuwardhani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This doctrinal legal research aims to analyze the authority of the Regional Supervisory Council (Majelis Pengawas Daerah/MPD) in retrieving notarial protocols that are 25 years old or older, as regulated under Article 63 paragraphs (5) and (6) of Law Number 2 of 2014 concerning the Amendment to Law Number 30 of 2004 on the Office of Notary. The study employs a statutory and conceptual approach, analyzed through legal interpretation and deductive syllogism methods. The findings indicate a normative ambiguity in Article 63 paragraph (5) regarding the authorized recipient of such protocols and a disharmony between this provision and Article 30 letter c of the Minister of Law and Human Rights Regulation Number 24 of 2020. The latter merely authorizes MPD to determine the storage location of the protocols without explicitly granting the authority to retrieve them. This discrepancy potentially weakens MPD’s supervisory function and creates a legal vacuum concerning the responsibility for the preservation of notarial archives. Therefore, regulatory reform through harmonization of implementing regulations is necessary to ensure consistency with the legislative mandate, thereby safeguarding the legal protection, continuity, and security of state documents in the form of notarial protocols